Patterns of T cell co-stimulation and co-inhibition in tumor microenvironment conditions, in vitro - Guerra, Luana Frias, 1992- (2015)
Tese de mestrado. Biologia (Biologia Molecular e Genética). Universidade de Lisboa, Faculdade de Ciências, 2015